2018
DOI: 10.1002/asia.201801031
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sulfur‐Containing Diamino Acid Structure on Covalently Crosslinked Copolypeptide Hydrogels

Abstract: Biologically occurring non‐canonical di‐α‐amino acids were converted into new di‐N‐carboxyanhydride (di‐NCA) monomers in reasonable yields with high purity. Five different di‐NCAs were separately copolymerized with tert‐butyl‐l‐glutamate NCA to obtain covalently crosslinked copolypeptides capable of forming hydrogels with varying crosslinker density. Comparison of hydrogel properties with residue structure revealed that different di‐α‐amino acids were not equivalent in crosslink formation. Notably, l‐cystine w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…A strongly basic KOtBu initiator was also used to polymerize multiple di- N -carboxyanhydrides (di-NCAs) to prepare high molecular weight copolymers (Scheme 2(B)). 24 Apart from the above traditional initiator, hydroxyl-bearing PEG was applied in the ROP of Cys 2 NCA. 25 The reaction mixture was heated to 45 °C to accelerate the polymerization due to the relatively low reactivity of hydroxyl group.…”
Section: Controlled Synthesis Of Cystine-based Polypeptidesmentioning
confidence: 99%
See 2 more Smart Citations
“…A strongly basic KOtBu initiator was also used to polymerize multiple di- N -carboxyanhydrides (di-NCAs) to prepare high molecular weight copolymers (Scheme 2(B)). 24 Apart from the above traditional initiator, hydroxyl-bearing PEG was applied in the ROP of Cys 2 NCA. 25 The reaction mixture was heated to 45 °C to accelerate the polymerization due to the relatively low reactivity of hydroxyl group.…”
Section: Controlled Synthesis Of Cystine-based Polypeptidesmentioning
confidence: 99%
“…Notably, most of the polymerizations of Cys 2 NCA were usually incomplete, with conversion rates of around 70% to 80%, resulting from the formed networks that hindered the reaction between Cys 2 NCA and the embedded polymer chain end. 24 In a recent study reported by Deming's group, the monomer consumption and yield were evaluated in the copolymerization of different di-NCA monomers with Glu NCA using KOtBu as an initiator. 24 The yield could reach more than 90% when the molar percentage of di-NCA was lower than 5%.…”
Section: Controlled Synthesis Of Cystine-based Polypeptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with a batch reaction, the microflow strategy enabled the rapid preparation of various NCAs at room temperature. Different than the preparation of NCAs with acid labile-side chains in a batch reactor, which requires acid scavengers (e.g., α-pinene and triethylamine (TEA)) to remove acidic byproducts generated during NCA synthesis, the NCA synthesis in a microflow reactor employed a flash dilution step to protect the NCAs from being overexposed in an acidic environment, making it a facile and efficient method for the preparation of NCAs with acid-labile side chains (Figure b).…”
Section: Chemical Synthesismentioning
confidence: 99%
“…Cystine, the endogenous dimerized version of oxidized cysteine, is the only difunctional amino acid found in ribosomal‐derived proteins. Therefore, in polypeptide synthesis, it represents the most common difunctional amino acid feedstock that has been used in carboxyanhydride (NCA) preparation and synthesis . In particular, cystine NCA has been used in the development of a series of multifunctional polypeptides known as core‐crosslinked stars (CCS) or nanogels, which can be successfully designed using this crosslinker in the arm‐first method .…”
Section: Introductionmentioning
confidence: 99%